A Discussion of Possible Approaches to the Integration of Thermochemical Storage Systems in Concentrating Solar Power Plants - Lanchi, Michela; Turchetti, Luca; Sau, Salvatore; Liberatore, Raffaele; Cerbelli, Stefano; Murmura, Maria Anna; Annesini, Maria Cristina (Energies (Basel), 2020)
One of the most interesting perspectives for the development of concentrated solar power (CSP) is the storage of solar energy on a seasonal basis, intending to exploit the summer solar radiation in excess and use it in the winter months, thus stabilizing the yearly production and increasing the capacity factor of the plant. By using materials subject to reversible chemical reactions, and thus storing the thermal energy in the form of chemical energy, thermochemical storage systems can potentially serve to this purpose. The present work focuses on the identification of possible integration solutions between CSP plants and thermochemical systems for long-term energy storage, particularly for high-temperature systems such as central receiver plants. The analysis is restricted to storage systems potentially compatible with temperatures ranging from 700 to 1000 °C and using gases as heat transfer fluids. On the basis of the solar plant specifications, suitable reactive systems are identified and the process interfaces for the integration of solar plant/storage system/power block are discussed. The main operating conditions of the storage unit are defined for each considered case through process simulation.